THE USE OF CHLORELLA IN THE CULTIVATION OF CULTIVATED PLANTS (Scientific journal of the Fergana State University, 2023)
Chlorella is a small single-celled genus of green algae belonging to the class of chlorococci. Chlorella intensely absorbs solar energy. Its biomass contains 40-50 percent protein, 30-37 percent carbohydrates, 5-10 percent fat, vitamins and other substances. Up to 30-70 tons of biomass can be obtained from chlorella from the surface of one hectare of a water basin (April—November). The cultivation of chlorella suspension has formed a new direction of bioengineering in biology. The purpose of the study: To study the values and uses of chlorella in the cultivation of cultivated plants.Research methods: The methods proposed by academician A.M. Muzaffarov and Doctor of Biological Sciences, Professor T.T. Taubaev were used. In the following years, the nutrients recommended by them were further enriched by scientists of soil microbiology. Methods of feeding chlorella were developed at the Institute of Botany of the Academy of Sciences of the Republic of Uzbekistan, and then at the Institute of Microbiology.Conclusion: The use of chlorella will save millions of dollars on toxic chemicals, large profits in grain growing, fruit and vegetable growing, rice growing. Chlorella differs from crops grown in agriculture in that the amount of protein, fat and other nutrients contained in it can also change as the conditions of its cultivation change. This will allow in the future to obtain protein, fats, vitamins, antibiotics and other substances based on the cultivation of chlorella.